2017
DOI: 10.1242/jcs.206623
|View full text |Cite
|
Sign up to set email alerts
|

TRIM65 triggers β-catenin signaling via ubiquitylation of Axin1 to promote hepatocellular carcinoma

Abstract: Deregulation of ubiquitin ligases contributes to the malignant progression of human cancers. Tripartite motif-containing protein 65 (TRIM65) is an E3 ubiquitin ligase and has been implicated in human diseases, but its role and clinical significance in hepatocellular carcinoma (HCC) remain unknown. Here, we showed that TRIM65 expression was increased in HCC tissues and associated with poor outcome in two independent cohorts containing 888 patients. In vitro and in vivo data demonstrated that overexpression of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 31 publications
5
33
0
Order By: Relevance
“…25,26 β-Catenin can also be triggered by TRIM65 via enhancement of the ubiquitination of Axin1 in the progression of hepatocellular carcinoma. 27 In the present study, we found that β-catenin was down-regulated by TRIM32 knockdown in SGC7901 and AGS cells and was up-regulated in MKN28 cells with TRIM32 overexpression. In the nuclear fraction, β-catenin expression was also remarkably enhanced in cells with TRIM32 overexpression and decreased in cells with silenced TRIM32.…”
Section: Trim32 Promotes Gastric Tumour Growth In Vivosupporting
confidence: 55%
“…25,26 β-Catenin can also be triggered by TRIM65 via enhancement of the ubiquitination of Axin1 in the progression of hepatocellular carcinoma. 27 In the present study, we found that β-catenin was down-regulated by TRIM32 knockdown in SGC7901 and AGS cells and was up-regulated in MKN28 cells with TRIM32 overexpression. In the nuclear fraction, β-catenin expression was also remarkably enhanced in cells with TRIM32 overexpression and decreased in cells with silenced TRIM32.…”
Section: Trim32 Promotes Gastric Tumour Growth In Vivosupporting
confidence: 55%
“…BCL9L (B-cell CLL/lymphoma 9 like) protein shares a conserved domain with BCL9, which is related to intestinal tumor progression. TRIM65 can trigger -catenin signaling via ubiquitylation of Axin1 to promote hepatocellular carcinoma 11 .
Figure 3Neoantigen comparison between LN-negative and LN-positive breast cancer. ( A ) The boxplot of the number of neoantigen peptides.
…”
Section: Resultsmentioning
confidence: 99%
“…To this end, it is tempting to conclude that TRIM65 is an important hub for signaling cross talk in general, which also implies that the functions of TRIM65 in a physiological or disease context should be considered. For example, in a study by Yang et al [16], HMGA1 seems to be an upstream transcription factor (TF) for TRIM65 regulation. We looked for a correlation between HMGA1 and TRIM65 in both the TCGA CRC data set and our cohort, and failed to see evidence for that finding.…”
Section: Discussionmentioning
confidence: 99%
“…Like other TRIM members that are involved in the immune response, TRIM65 also participates in the virus-induced innate immune response by ubiquitination of substrate proteins [13, 14]. In tumor malignancies, TRIM65 was first shown to harbor oncogenic activities in lung and liver cancers, and cancer-related TRIM65 substrates, including TP53 and AXIN1, had been reported [15, 16]. More recently, TRIM65 was reported to support bladder urothelial carcinoma cell progression by targeting ANXA2 for ubiquitination and degradation [17].…”
Section: Introductionmentioning
confidence: 99%